2005
DOI: 10.1128/jcm.43.8.3595-3601.2005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of White-Tailed Deer with Anaplasma phagocytophilum , Etiologic Agent of Human Granulocytic Anaplasmosis

Abstract: Serologic and molecular evidence of Anaplasma phagocytophilum has been demonstrated in white-tailed deer (WTD; Odocoileus virginianus), and deer are an important host for the tick vector Ixodes scapularis. In this study, we describe experimental infection of WTD with A. phagocytophilum. We inoculated four WTD with a human isolate of A. phagocytophilum propagated in tick cells. Two additional deer served as negative controls. All inoculated deer developed antibodies (titers, >64) to A. phagocytophilum, as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 63 publications
2
25
0
1
Order By: Relevance
“…Our study demonstrates that both A. phagocytophilum strains are indeed present in Central and Western Wisconsin, and suggest that two novel variants exist in white-tailed deer that have never been described before. Though recent work by others suggests that the Ap-ha strain can infect white-tailed deer (Tate et al 2005), no evidence of natural infection with this strain has been found in our investigations or those of others (Belongia et al 1997;Massung et al 2002. As both the Ap-ha and Ap-Variant 1 strains were found in naturally infected ticks in both regions of the state, we propose that transmission of both strains is occurring between ticks and wild mammals, and that humans in both places could possibly be at risk for contracting HGA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates that both A. phagocytophilum strains are indeed present in Central and Western Wisconsin, and suggest that two novel variants exist in white-tailed deer that have never been described before. Though recent work by others suggests that the Ap-ha strain can infect white-tailed deer (Tate et al 2005), no evidence of natural infection with this strain has been found in our investigations or those of others (Belongia et al 1997;Massung et al 2002. As both the Ap-ha and Ap-Variant 1 strains were found in naturally infected ticks in both regions of the state, we propose that transmission of both strains is occurring between ticks and wild mammals, and that humans in both places could possibly be at risk for contracting HGA.…”
Section: Discussionmentioning
confidence: 99%
“…While the white-footed mouse is likely the dominant small-mammal reservoir, infection is usually transient, unlike the chronic infection observed with B. burgdorferi (Goodman 2005). White-tailed deer are important for the maintenance of Ixodes populations, but the role these large mammals play in the life cycle of A. phagocytophilum is unclear (Massung et al 2005;Tate et al 2005;Rainwater et al 2006). White-tailed deer may be seropositive and/or PCR positive for A. phagocytophilum (Bouchard et al 2013).…”
Section: Human Granulocytic Anaplasmosis (Hga)mentioning
confidence: 99%
“…of raccoons, Ehrlichia chaffeensis, E. canis, E. ewingii, Anaplasma phagocytophilum, and Borrelia spp. (Little et al 1998, Dugan et al 2005, Tate et al 2005, Moyer et al 2006, and by indirect fluorescent antibody (IFA) testing for antibodies reactive against E. chaffeensis, A. phagocytophilum, and Borrelia spp. as described with modifications (Comer et al 2000, Yabsley et al 2003, Dugan et al 2005, Tate et al 2005, Moyer et al 2006).…”
Section: Animals and Proceduresmentioning
confidence: 99%